2023
DOI: 10.3389/fmicb.2023.1108651
|View full text |Cite
|
Sign up to set email alerts
|

The phylogeny and metabolic potentials of an n-alkane-degrading Venatorbacter bacterium isolated from deep-sea sediment of the Mariana Trench

Abstract: Recently, several reports showed that n-alkanes were abundant in the hadal zone, suggesting that n-alkanes could be an important source of nutrients for microorganisms in hadal ecosystems. To date, most of the published studies on the microbial capacity to degrade hydrocarbons were conducted only at atmospheric temperature and pressure (0.1 MPa), and little is known about whether and which microbes could utilize n-alkanes at in situ environmental conditions in the hadal zone, including low temperature and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Compatible solutes, commonly referred to as osmoprotectants, are low molecular weight, highly soluble organic compounds that mainly protect microorganisms from a variety of environmental stresses, such as drought, high salt, low or high temperature, HHP, and heavy metals [ 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. In this study, we found that strain M8S5 possesses 21 genes to transport diverse kinds of compatible solutes, including glycine betaine/carnitine/choline, proline, sarcosine, and trehalose ( Figure 4 and Supplementary Table S14 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compatible solutes, commonly referred to as osmoprotectants, are low molecular weight, highly soluble organic compounds that mainly protect microorganisms from a variety of environmental stresses, such as drought, high salt, low or high temperature, HHP, and heavy metals [ 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. In this study, we found that strain M8S5 possesses 21 genes to transport diverse kinds of compatible solutes, including glycine betaine/carnitine/choline, proline, sarcosine, and trehalose ( Figure 4 and Supplementary Table S14 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a total of five genes encoding molecular chaperones, including dnaJK , grpE , htpG , and hslO , were predicted in strain M8S5 ( Supplementary Table S14 ). These molecular chaperones may be induced by high-pressure and low-temperature stresses, help proteins to fold correctly, and maintain protein function [ 87 , 92 , 95 ]. Also, two genes related to cold shock proteins ( cspA ) were detected in the genome of strain M8S5 ( Supplementary Table S14 ), which may serve as cryoprotectants in low-temperature adaptation [ 96 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the biodegradable structural group, n-alkanes are the most susceptible to biodegradation, except for C20-C40, which are hydrophobic solids and are not easily degraded [46]. Another major group of petroleum hydrocarbons are polycyclic aromatic hydrocarbons (PAHs), which are partially recalcitrant to biodegradation.…”
Section: Diatom Microalgae: Attributes and Potential For The Biodegra...mentioning
confidence: 99%
“…Short-chain alkanes are aliphatic hydrocarbons and are the most easily degraded, followed by alkanes with side chains or branched alkanes and then aromatic hydrocarbons with stable ring structures. Although alkanes have been reported in groundwater, rivers, lakes, oceans, and soil [46], they may also occur in aquatic organisms and sediments (estuarine, marine, and riverine). Alkanes with chains of up to 44 carbon atoms are susceptible to microbial degradation; however, only a limited number of species can use Cl-C4 and C5-C9 alkanes because of their toxicity [93,94].…”
Section: Diatoms-origin and Producers Of Isoprenoids Alkanes And Alkenesmentioning
confidence: 99%